Total Stripping of the Great Saphenous Vein in Varicose Vein Patients with Thrombophlebitis - T. M. Murasov; M. V. Timerbulatov; S. S. Kazbulatov; A. M. Murasov; D. R. Ibragimov (Креативная хирургия и онкология, 2024)
Introduction. Patients with varicose disease of the lower extremities may suffer from subcutaneous vein thrombophlebitis with an incidence of more than 50%. However, saphenous vein thrombophlebitis occurs against the background of varicose veins in 80% of patients. Aim. To improve the efficacy of phlebectomy in patients with varicose veins complicated by saphenous vein thrombophlebitis. A modified method of total stripping of the great saphenous vein was developed and introduced into clinical practice in City Clinical Hospital No. 21 (Ufa, Russia). The modified surgical technique is aimed at reducing the severity of postoperative hematomas, increasing the cosmetic effect and reducing the incidence of damage to the cutaneous nerve located near the large saphenous vein. The surgery technique was patented (Patent No. RU2812293C1). Materials and methods. From 2022 to 2023, total stripping of the great saphenous vein was performed in 26 patients with varicose veins of the lower extremities and thrombophlebitis of the great saphenous vein in Cardiac Surgery Department of City Clinical Hospital No. 21. The examined patients were divided into a control group (18 patients) and a comparison group (8 patients). The quality of life of all patients was assessed before and after surgical intervention using the Visual Analog Scale (VAS). Results and discussion. All patients underwent total stripping of the great saphenous vein. Prior to surgery, no statistically significant difference was reported in the assessment of quality of life between the groups. The group of the modified stripping technique demonstrated positive clinical and aesthetic results after surgery. Performing total stripping of the great saphenous vein using the modified technique statistically significantly improved the quality of life in the postoperative period. Control points of examinations were on days 1, 7, 30, 90 after surgery. Conclusion. The comparative analysis of the treatment results proved the efficacy of the modified technique of total stripping in varicose vein patients with thrombophlebitis, including a higher level of quality of life, better clinical and aesthetic result of surgical treatment.